PENGARUH NORMA SUBJEKTIF, KEWAJIBAN MORAL DAN PEMAHAMAN PERATURAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA MAKASSAR UTARA - Sitti Rahma Sudirman; Darwis Lannai; Hajering Hajering (Universitas Muhammadiyah Makassar, 2020)
The purpose of this research is to identify and analyze the influence of subjective norms, moral obligation, and taxpayer formal compliance towards the compliance of tax payers in KPP Pratama Makassar Utara. The data required in this study is primary data in the form of respondents’ assessment of subjective norms, moral obligation, taxpayer formal compliance and the compliance of tax payers in KPP Pratama Makassar Utara. Data collection methods used in this study is the questionnaire as well as a literature review on the books related to the subject matter covered. Data analysis techniques used by Multiple Linear Regression Test, t test, F test, Coefficient of Determination Test. The result shows that simultaneously, subjective norms, moral obligation, and taxpayer formal compliance are influential towards the compliance of tax payers in KPP Pratama Makassar Utara. Meanwhile the result of partial test (t-test) shows that subjective norms and moral obligation are partially have significant and positive influences towards the compliance of tax payers. Taxpayer formal compliance on the other hand, partially has positive and insignificant influence towards the compliance of tax payers.